Emergence of practical fluorescence in a confined space of nanoporous silica: significantly enhanced quantum yields of a conjugated molecule. Issue 97 (23rd November 2021) - Hayashi, Kosei; Fujimaki, Yasuto; Mishiba, Kentaro; Watanabe, Hiroto; Imai, Hiroaki
Abstract : The fluorescence of benzanthrone, which is a conjugated molecule bearing a carbonyl group, is activated by confinement in a pore with a diameter close to the molecular size. Abstract : The fluorescence of benzanthrone, which is a conjugated molecule bearing a carbonyl group, is activated by confinement in a pore with a diameter close to the molecular size. An intense emission originating from the aromatic character π–π* transition is achieved through suppression of the nonradiative n–π* transition by strong hydrogen bonding between carbonyl groups and silanol groups with a micropore-filling effect in the nanospace.